PENGARUH MOTIVASI, KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA CV. MEDALI MAS - Sandiawan, Zogi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to analyze motivation, compensation and work discipline on the work productivity of employees at CV. Medali Mas. This research was conducted with an inferential quantitative approach and used primary and secondary data. The sample used was 40 respondents with a simple random sampling method. Data were analysed by descriptive statistics, classical assumption test, multiple linear regression, determinant coefficients and hypothesis testing. The results showed that compensation variable had no effect on employee work productivity, motivation and work discipline variables had an effect on employee work productivity. The relationship between the variables of motivation, compensation and work discipline simultaneously has a significant effect on employee productivity. The results of this study differ from the reference which shows that there is an effect of compensation on work productivity. Means that managers can increase productivity with compensation according to the ability of CV. Medali Mas.